2007
DOI: 10.1088/0957-4484/19/03/035503
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteria based on the thermomechanical noise of a nanomechanical resonator: origin of the response and detection limits

Abstract: We have measured the effect of the bacteria adsorption on the resonant frequency of microcantilevers as a function of the adsorption position and vibration mode. The resonant frequencies were measured from the Brownian fluctuations of the cantilever tip. We found that the sign and amount of the resonant frequency change is determined by the position and extent of the adsorption on the cantilever with regard to the shape of the vibration mode. To explain these results, a theoretical one-dimensional model is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 23 publications
3
77
1
Order By: Relevance
“…The eigenfrequencies of the microcantilever are shifted due to the mass and mechanical stiffness of the adsorbate. [7][8][9][10][11][12] The static deformation originates as the outcome of intermolecular interactions between the adsorbed molecules themselves and their interaction with the surface of the microcantilever. Depending on the free surface energy variation and the dimensions and mechanical properties of the cantilever, molecular adsorption typically induces cantilever displacements from few to hundreds of nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…The eigenfrequencies of the microcantilever are shifted due to the mass and mechanical stiffness of the adsorbate. [7][8][9][10][11][12] The static deformation originates as the outcome of intermolecular interactions between the adsorbed molecules themselves and their interaction with the surface of the microcantilever. Depending on the free surface energy variation and the dimensions and mechanical properties of the cantilever, molecular adsorption typically induces cantilever displacements from few to hundreds of nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Tamayo have published several works outlining the effects of adsorption position on the resonance response of cantilevers. [37][38][39] In these works, it has been shown that the deposition of bacterial cells can produce both negative ("mass effect") and positive ("stiffness effect") frequency shifts. It is proposed that the stiffness (Young's modulus) of the adsorbed particle alters the flexural rigidity of the cantilever to produce positive frequency shifts.…”
Section: Multimode Aspergillus Niger Growth Detection and Monitoringmentioning
confidence: 99%
“…Within the latter category, a large subset of sensing applications exists in the fields of proteomics [1][2][3][4][5], genomics [6][7][8] and microbiology [9][10][11][12][13][14][15], amongst others. A crucial component in achieving biologically relevant metrics in bio-sensing is the environment in which the test is performed.…”
Section: Introductionmentioning
confidence: 99%